Nanoliposomes as a Therapeutic Tool for Alzheimer’s Disease - Ordóñez-Gutiérrez, Lara; Wandosell, Francisco (Frontiers in Synaptic Neuroscience, 2020)
Abstract The accumulation of extracellular amyloid-beta (Aß), denoted as senile plaques, and intracellular neurofibrillary tangles (formed by hyper-phosphorylated Tau protein) in the brain are two major neuropathological hallmarks of Alzheimer's disease (AD). The current and most accepted hypothesis proposes that oligomerization of Aß peptides triggers the polymerization and accumulation of amyloid, which leads to the senile plaques. Several strategies have been reported to target Aß oligomerization/polymerization. Since it is thought that Aß levels in the brain and peripheral blood maintain equilibrium, it has been hypothesized that enhancing peripheral clearance (by shifting this equilibrium towards the blood) might reduce Aß levels in the brain, known as the sink effect. This process has been reported to be effective, showing a reduction in Aß burden in the brain as a consequence of the peripheral reduction of Aß levels. Nanoparticles may have difficulty to cross the blood-brain barrier (BBB), initially due to their size. It is not clear whether particles in the range of 50-100 nm should be able to cross the BBB without being specifically modified for it. Despite the size limitation of crossing the BBB, several nanoparticle derivatives may be proposed as therapeutic tools. The purpose of this review is to summarize some therapeutic approaches based on nanoliposomes using two complementary examples: First, unilamellar nanoliposomes containing A generic ligands, such as sphingolipids, gangliosides or curcumin, or some sphingolipid bound to the binding domain of ApoE; and second, nanoliposomes containing monoclonal antibodies against Aß. Following similar rationale nanoparticles of poly(lactide-co-glycolide)-poly (ethylene glycol) conjugated with curcumin-derivate (PLGA-PEG-B6/Cur) were reported to improve the spatial learning and memory capability of APP/PS1 mice, compared with native curcumin treatment . In addition some new nano-structures such as exosomes, has been proposed as a putative therapeutic and prevention strategies of AD. Although the unquestionable interest of this issue is beyond the scope of this review. The potential mechanisms and significance of nanoliposome therapies for AD, which are still are in clinical trials, will be discussed.